Targeting DNA Gyrase to Combat Mycobacterium tuberculosis: An Update - Das, Swetarka; Garg, Tanu; Srinivas, Nanduri; Dasgupta, Arunava; Chopra, Sidharth (Current Topics in Medicinal Chemistry, 2019)
DNA gyrase is a clinically validated drug target, currently targeted only by fluoroquinolone class of antibacterials. However, owing to increasing drug resistance as well as a concomitant reduction in the availability of newer classes of antibiotics, fluoroquinolones are increasingly being over-utilized in order to treat serious infections, including multi-drug resistant tuberculosis. This, in turn, increases the probability of resistance to fluoroquinolones, which is mediated by a single amino acid change in gyrA, leading to class-wide resistance. In this review, we provide an overview of the recent progress in identifying novel scaffolds which target DNA gyrase and provide an update on their discovery and development status.
Keywords: Pathogen